Cochrane Database of Systematic Reviews 2011
DOI: 10.1002/14651858.cd009317
|View full text |Cite
|
Sign up to set email alerts
|

Psychological, social and welfare interventions for psychological health and well-being of torture survivors

Abstract: Johnson 2008 Johnson H, Thompson A. The development and maintenance of post-traumatic stress disorder (PTSD) in civilian adult survivors of war trauma and torture: a review.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 22 publications
0
17
0
2
Order By: Relevance
“…In addition, the authors called for studies of more homogeneous patient populations. While research on other groups of PTSD patients has burgeoned since, intervention studies concerning trauma-affected refugees are still limited in number and quality, and the vast majority are on psychological interventions only [12, 13]. …”
Section: Introductionmentioning
confidence: 99%
“…In addition, the authors called for studies of more homogeneous patient populations. While research on other groups of PTSD patients has burgeoned since, intervention studies concerning trauma-affected refugees are still limited in number and quality, and the vast majority are on psychological interventions only [12, 13]. …”
Section: Introductionmentioning
confidence: 99%
“…What the clinician assessing and treating pain needs to appreciate is that the field of post-traumatic stress is subject to strongly held beliefs, with some vested interests propagating particular treatment models [66], without either evidence for their superiority in general [67] or their suitability for torture survivors and military veterans. A systematic review and meta-analysis [67] found no immediate treatment effects of psychological treatments in nine randomised controlled trials on post-traumatic symptoms, general distress, or quality of life in torture survivors, and only very weak effects on post-traumatic symptoms and distress at follow-up.…”
Section: Psychological Statementioning
confidence: 99%
“…A systematic review and meta-analysis [67] found no immediate treatment effects of psychological treatments in nine randomised controlled trials on post-traumatic symptoms, general distress, or quality of life in torture survivors, and only very weak effects on post-traumatic symptoms and distress at follow-up. The trials were mostly of narrative exposure therapy, currently the dominant model and subject to critical commentary [67, 68, 69•].…”
Section: Psychological Statementioning
confidence: 99%
“…Für Folteropfer, die eine weitere Subgruppe komplex traumatisierter Menschen darstellen, kommen Patel et al (2014) in einem Cochrane-Review von 9 kontrollierten und randomisierten Studien zu der Aussage, dass eine vergleichsweise schlechte und hinsichtlich der genutzten Methoden und Verfahren inhomogene Datenlage vorliegt. Zumindest in den Follow-up-Messungen nach 6 Monaten lassen sich für 3 berücksichtigte Studien zur narrativen Expositionstherapie und für eine Studie zur kognitiven Verhaltenstherapie mittlere Effektstärken in der Reduktion von PTBS-Symptomen (0,52) zeigen.…”
Section: Kriterien/symptome Erläuterungenunclassified